Cog in the Wheel of Patronage. (November 2017) - Sanan, Deepak
This is a brief history of a career in the generalist higher civil service of India called the Indian Administrative Service (IAS). The article brings out the incentive structure which confronts a civil servant seeking to deliver better outcomes in the making and implementation of public policy in India. The peculiarities of India's federal system of inter-governmental transfers, the constraints, dilemmas and limited scope for making a difference, are all explored in an anecdotal format in this first-person account of a career spanning three and a half decades. The author begins with his reasons for joining the civil service, his initial years of heading the local administration in remote mountain areas and moves on to an analysis of various postings at state and central levels, including stints in finance, rural and urban development, water, sanitation, health, land and power sectors. Each segment attempts to explain different facets and nuances of both the limits and potential of a career choice in the premier civil service of India.